Associação entre a qualidade da dieta e fatores de risco cardiovascular de indivíduos dislipidêmicos - Costa, Leticia Sayuri Adama (2020)
Cardiovascular diseases (CVD) are the main causes of death worldwide. One of the main risk factors for CVD is dyslipidemia and the eating pattern can influence its onset. Objective: To analyze the association between diet quality and cardiovascular risk indicators in adults with dyslipidemia. Methods: This is a crosssectional study, with individuals aged between 20 and 59 years old who have some alteration in their lipid profile. Anthropometric and body composition and biochemical measurements were taken. To assess food consumption, the Food Frequency Questionnaire (FFQ) was used, validated for the Cuiabana population and afterwards, the Revised Diet Quality Index (IQD-R) adapted for the Brazilian population was calculated. The risk factor adopted was: BMI indicative of overweight, body fat percentage, waist circumference, waist-to-hip ratio, waist-to-height ratio, TG / HDLc ratio, blood pressure and fasting blood glucose. Data were presented as mean and standard deviation or median and interquartile range. Student t test and Mann-Whitney were used for comparisons for means and medians, respectively. For correlations, Pearson or Spearman tests were used according to distribution. A statistical significance level of 5% was adopted for all tests. Results: Results: 102 individuals with dyslipidemia were evaluated, 54.9% female and 45.1% male, with a mean age of 40,4±10,9 years. 83.4% of the individuals were overweight, 72.5% increased waist circumference, 83.6% with high levels of CRP. The average IQD-R was 70,80±42,98- 86,69 points with a range of 42.98 and 86.69 points, with no difference between genders. The group with the highest IQD-R score obtained higher concentrations of monocytes and serum magnesium, percentage of carbohydrates, fiber consumption, vitamin B6 and manganese, as well as lower consumption of percentage of lipids, saturated fatty acid, trans fats when compared to the group lowest score. There was no correlation between the quality of the diet and cardiovascular risk factors (p>0.05). Conclusion: Individuals are at risk for cardiovascular diseases according to anthropometric, biochemical and food consumption measures, however, there was no relationship between the quality of the diet and cardiovascular risk factors.